Control of an Ac-Ac Modular Multilevel Converter for Medium Frequency Applications - Diaz-Diaz, M; Ravet-Orellana, T (Institute of Electrical and Electronics Engineers Inc., 2024)
Modular Multilevel Converters (MMCs) have emerged as a key technology for high-power applications such as high-voltage transmission, wind energy conversion, large drive motors, and static compensators. Recently, MMCs have been proposed in applications of solid-state transformers and electric vehicle charging systems where medium-frequency transformers are required. Therefore, the conventional control and modulation of MMCs have to generate an alternating current port at medium frequency. Consequently, this paper proposes a novel control strategy for MMCs designed to generate a medium-frequency port while effectively regulating the converter. The control is based on a decoupled model of the MMC, which allows the regulation of the floating capacitor without relying on mitigation variables at the medium frequency. The modulation strategy is based on Phase-Shift Pulse Width Modulation (PS-PWM). Simulation results for a 1 MW MMC validate the control strategy performance, while experimental results using a 10 kW prototype confirm its practical feasibility and effectiveness. © 2024 IEEE